2014
DOI: 10.1007/s11999-013-3331-x
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Versus Replacement of Radial Head in Terrible Triad: Is There a Difference in Elbow Stability and Prognosis?

Abstract: Background Surgical treatment for terrible triad injuries of the elbow (defined as elbow dislocations with concomitant fractures of the radial head and coronoid) remains a challenging clinical problem. Specifically, the question of whether to repair or replace the radial head remains controversial. Questions/purposes We compared patients with terrible triad injuries of the elbow whose radial head fracture was treated with either internal fixation and internal fixation (ORIF) or radial head arthroplasty in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 21 publications
1
70
0
4
Order By: Relevance
“…They suggested that the improved visualization of the coronoid during radial head excision and replacement led to more accurate internal fixation. It may also result in less soft tissue stripping and subsequently less instability after radial head arthroplasty [19]. In another study, Leigh and Ball [20] demonstrated no difference in outcomes between radial head arthroplasty and internal fixation in a retrospective, nonrandomized study.…”
Section: Terrible Triadmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that the improved visualization of the coronoid during radial head excision and replacement led to more accurate internal fixation. It may also result in less soft tissue stripping and subsequently less instability after radial head arthroplasty [19]. In another study, Leigh and Ball [20] demonstrated no difference in outcomes between radial head arthroplasty and internal fixation in a retrospective, nonrandomized study.…”
Section: Terrible Triadmentioning
confidence: 99%
“…Attempts at internal fixation for radial head fractures with more than three articular fragments have been associated with unsatisfactory results [18]. Using this as one indication for radial head arthroplasty, Watters et al [19] found no difference in functional outcomes or elbow motion compared to internal fixation after a mean follow-up of 24 months. Interestingly, the authors reported three elbows with persistent instability in the internal fixation group compared to no cases in the arthroplasty group [19].…”
Section: Terrible Triadmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, 2 retrospective studies exist comparing ORIF to radial head arthroplasty and neither found significant differences in outcomes at short-term follow-up. 67,68 Oversizing of the Fig. 11.…”
Section: Mason III and Ivmentioning
confidence: 99%
“…Die Versorgung von komplexen Frakturen des Ellenbogens hat über die letzten Jahre mit der Einführung von winkelstabilen und anatomisch präformierten Implantaten für Radiuskopf-, Koronoidund Olekranonfrakturen, der Weiterentwicklung von Radiuskopfprothesen sowie dem besseren biomechanischen Verständnis der knöchernen und weichteiligen Gelenkstabilisatoren eine stetige Verbesserung erfahren [4,7,29,32,33,36,49]. Fälle übersehener oder initial fehleingeschätzter Instabilitäten sind selten, sie können jedoch zu einer chronischen Subluxations-oder Luxationsstellung des Ellenbogengelenkes führen.…”
Section: Introductionunclassified